Скандал в эго-документах позднесоветских писателей: попытка “насыщенного описания” - Maria Mayofis (eSamizdat)
The article explores the nuanced meanings of ‘scandal’ within the late Soviet writers’ milieu. By carefully examining word usage within the specific era and cultural context, the author demonstrates that during the late Soviet period, literary scandal was deeply intertwined with the concept of censorship. In certain instances, a literary scandal was anticipated following the publication of ‘dangerous’ or ‘undesirable’ texts that potentially challenged the ideological purity and ethical integrity of the Soviet system – a meaning relatively consistent across early and late Soviet periods. At times, a scandal was expected as a consequence of publicizing the very fact of literary censorship and the suppression of works in the USSR, as well as the persecution of writers for their literary output. Since the primary audience for such scandals was international public opinion, prominent writers frequently leveraged the threat of an ‘international scandal’ to secure desired outcomes from editors, censors, and – most critically – special ‘curators’ responsible for overseeing literature on behalf of the Central Committee of the Communist Party. The article suggests that from the mid-1950s onward, Soviet writers began to strategically instrumentalize the concept of literary scandal, even asserting that party and literary officials themselves provoked such controversies through excessive prohibitive measures and violations of established ‘rules of the game’.